The monetary control framework of Guyana : experiences, lessons and consequences - Khemraj, Tarron (2006)
Examines the monetary policy framework of Guyana. Proposes several factors that might account for the persistently high levels of excess liquidity. Argues that it is not automatic that the excess liquidity is driving the rate of inflation. Investigates the factors which account for variations in excess reserves.